Effect of Spacing on Growth and Yield of Five Bambara Groundnut (Vigna Subterranea (L) Verdc.) Landraces (Journal of Science and Technology, 2016)
An experiment was conducted under field conditions to study the effect of spacing on yield of five bambara groundnut landraces in 2008 cropping season. The experimental design was a split plot with bambara groundnut landraces; Nav 4, Nav Red, Black eye, Mottled cream and Burkina as the main plot factor and the three spacings (50 x 20cm, 50 x 30cm, 50 x 40cm) as the subplot factor. Sowing was done on the 17th of May 2008 at two seeds per hill and thinned to one seedling per hill 21 days after sowing (DAS). Growth analysis were carried out at six different sampling periods during which canopy spread, petiole length, leaf area index (LAI), total dry matter were measured. Yield data on number of plants per metre squared, number of pods per plant, number of seeds per pod, mean seed weight as well as harvest index (HI) were also taken at harvest. Results indicated that the lower spacing of (50cm x 20cm) produced significantly (P < 0.05) the greatest pod and grain yield of 3399kg/ha and 1684.7kg/ha respectively. The same treatment also produced significantly higher number of pods than the higher spacing treatments. However, the number of seeds per pod and mean seed weight were not affected by spacing. Although, most vegetative data were not significantly affected by varying plant spacing, leaf area index was significantly highest at 50cm x 20cm than the other treatments. Among the landraces, Mottled Cream recorded significantly the highest shelling percentage of 70.6% and HI of 64.9. Based on high shelling percentage, HI and mean seed weight, Mottled Cream produced the highest seed yield (1656kg/ha). The optimum spacing for the highest pod yield in this study was 50cm x 20cm.